Study of the performance of Pt catalysts supported on activated carbon felt and granular carbon for nitrobenzene hydrogenation - Vilella, Irene María Julieta (2005)
The catalytic behavior of the Pt (1 wt%) catalysts supported on purified activated carbon felt (ACF) and powder carbon (C) has been studied in the nitrobenzene (NBZ) hydrogenation reaction in liquid phase after activation under a H2 atmosphere between 298 and 623 K. Hydrogen chemisorption measurements, temperature-programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS) were used to characterize the metallic phase of the catalysts. For Pt/ACF catalysts, the catalytic activity in nitrobenzene hydrogenation after reduction at 298 K was very high and it decreased as the reduction temperature increased up to 373 K. On the other hand, the Pt/C catalyst after reduction at 298 K was inactive. The activity of the Pt/C catalysts increased in a moderate way when the reduction temperature increases up to 373 K. Between 373 and 623 K of reduction temperature, the hydrogenation rate was modified in a minor proportion for both catalysts. The Pt/ACF catalyst previously reduced at 298 K showed a lag step before the reaction ignition. This effect could be attributed to the tendency the metallic centers have to conform the proper arrangement to hydrogenate the nitrobenzene molecule.